2013
DOI: 10.1371/journal.pone.0075681
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Receptor of Hyaluronan-Mediated Motility (RHAMM) on Human Urothelial Transitional Cell Cancer of the Bladder

Abstract: Hyaluronan (HA) is a carbohydrate of the extracellular matrix with tumor promoting effects in a variety of cancers. The present study addressed the role of HA matrix for progression and prognosis of human bladder cancer by studying the expression and function of HA-related genes.MethodsTissue samples of 120 patients with different stages of transitional cell bladder cancer, who underwent surgical treatment for bladder cancer at the University Hospital of Essen were analysed. mRNA-expression levels of HA syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…breast, stomach or colorectal cancers, and in multiple myelomas. A previous CD168 knockdown study demonstrated growth reduction of transplanted tumors (28). Increased CD168 expression was revealed to be indicative of an elevated, or abnormal, level of cell proliferation in human OSCC (17).…”
Section: Discussionmentioning
confidence: 77%
“…breast, stomach or colorectal cancers, and in multiple myelomas. A previous CD168 knockdown study demonstrated growth reduction of transplanted tumors (28). Increased CD168 expression was revealed to be indicative of an elevated, or abnormal, level of cell proliferation in human OSCC (17).…”
Section: Discussionmentioning
confidence: 77%
“…Hyaluronan synthase 3 (HAS3) is one of the three HAS isoforms producing HA. HAS3 had been investigated in many cancers [16][17][18][19][20][21]38]. No study, however, has found consistent results of HAS3 effects on different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…3 Kaplan-Meier plots demonstrates the prognostic significances of HAS3 immunoexpression for diseasespecific survival and metastasisfree survival in UTUC (a, b) and UBUC (c, d), respectively growth or to overexpression in cancer compared to a normal organ [16,17,[19][20][21]. Contrariwise, other research has suggested that HAS3 is significantly reduced in premalignancy or malignancy compared to its benign counterparts [18,38]. In the present study, HAS3 underexpression was significantly associated with adverse clinicopathological parameters, i.e., higher pT status, nodal metastasis, high histological grade, vascular invasion, and frequent mitoses in both UTUCs and UBUCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations